Experimental study on sorption–desorption characteristics of natural composite desiccant with metal embedment. (25th June 2023) - Dasar, Sangappa R.; S., Anish; Kadoli, Ravikiran; Yadav, Ajay K.
Abstract: The present study investigates the effect on total moisture sorption, moisture sorption rate, moisture desorption rate, and reduction in the temperature of dehumidified air of metal-embedded natural composite desiccants (MENCDs), which can be used in dehumidification systems. A natural composite desiccant, in which the unutilized portion of the spherical desiccant material is replaced with a metallic ball, is proposed. Stainless steel balls with a diameter of 4.75 and 6.35 mm are used to make different thickness ratios (TR = 1, 0.525, and 0.365) of MENCDs. The natural composite desiccant is prepared from dried cow dung and polyvinyl pyrrolidone with a ratio of 3:1. Experiments are conducted to find the optimum thickness ratio of MENCDs. The total moisture sorption, moisture sorption rate, total heat load reduction, and exergy efficiency of these dehumidification systems are investigated under different relative humidities (RH = 65% to 85%), and at a constant temperature and velocity. Desorption characteristics are tested under 328 K and 5% RH. The total moisture sorption of MENCDs with a TR of 0.365 is found to be 11.84 g/100 g, which is 17% higher compared to natural composite desiccants (i.e., TR = 1) at 85% RH, whereas, the total moisture sorption rate is 0.4 g/100 g ⋅ min, which is 20.57% higher for TR of 0.365 compared to TR = 1. Moisture desorption rate for TR = 0.365 is 16.66% higher compared to TR = 1. The average exergy efficiency of these systems is 60%. The average exergy efficiency of these composite desiccants with a TR = 0.365 is 9.6% higher compared to TR = 1. The average total heat load reduction for composite desiccants with a TR = 0.365 is 24% higher compared to TR = 1. The experimental study shows that the MENCDs will help to increase total heat load reduction, sorption and desorption rate, and total moisture sorption of dehumidified air with optimum thickness ratio for enhanced utilization of a composite desiccant for dehumidification systems. Highlights: Metal-embedded natural composite desiccant is prepared and studied. Sorption–desorption characteristics of desiccant are obtained experimentally. The maximum moisture sorption of the desiccant is enhanced by 17%. The moisture sorption rate of the desiccant is improved by 20%. Total heat load reduction and exergy analysis of the system is presented.